The urgency to reform the kafāla system in the sake of human rights of Indonesia domestic workers - Anggita Doramia Lumbanraja; Yusriyadi Yusriyadi (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2021)
The Maṣlaḥa of Indonesian Foreign Domestic Workers in Saudi Arabia still become the biggest concern. Even though Saudi Arabia has reformed the Labor Law on the kafāla system, unfortunately, it is excluded from Foreign Domestic Workers. Therefore, it urges legal research to examine the kafāla system in Saudi Arabia from an Islamic and human rights perspective. Then, to provide the strategic plans for the Indonesian government to do. This research uses doctrinal research methods through the literature study and analyzed with the qualitative descriptive method. From the Islamic law perspective, although the kafāla system in Saudi Arabia is derived from the Qur'an and the Sunnah. Kafāla system in Saudi Arabia is regulated on Resolution no. 310. However, in practice, Kafil abuses their strong position (83. QS. Al-Mutaffifin) in treating workers arbitrarily. In other words, there is a deviation from the philosophical values of maqāṣid ash-syarīʿah. From the international law perspective, this practice is against the mandate of the UDHR and ICCPR. Therefore, it is highly recommended that Indonesia push Saudi Arabia to replace individual sponsorship as Kafil for Indonesian Domestic Workers. It is better to establish a special guarantee institution for Domestic Workers from Indonesia in Saudi Arabia integrated with the SPSK System.